The Status of Pre-Islamic Arab Women: Reform and the Challenge of Fulfilling Women's Rights in Contemporary Islamic Family Law Practice - Henri Bimawan; Muhammad Haeqhal; Marhadi; Rafi Kusuma F.R; Try Rama Bagus Sanjaya (Legitima : Jurnal Hukum Keluarga Islam, 2025)
Purpose - This study aims to analyze the social status of Arab women during the Jahiliyyah period, within the context of the patriarchal social system that dominated Arab society at that time, and to evaluate how these conditions influenced the development of contemporary Islamic family law, particularly in terms of fulfilling women's rights. Methods - The research method used was a literature study with a historical approach. The primary data in this study consisted of verses from the Qur'an, while the secondary data included scientific references related to the research theme. Data were collected using documentation techniques and analyzed using content analysis techniques. Findings - The status of women in pre-Islamic Arabia was very marginalized, and they did not have proper legal status (in terms of inheritance, marriage, and social status). The arrival of Islam brought significant changes that improved the status of women by granting them basic rights. Reform efforts undertaken by Muslim countries, such as restrictions on polygamy, child custody rights, and fairer inheritance rules, are manifestations of the spirit of the Qur'an in creating justice and protecting women's rights. Research implications - Practically, the findings can be used as a basis for normative reflection for family law legislation with a gender justice perspective in contemporary Muslim societies. Originality/value - The originality of this research lies in its critical approach to the dominant narrative about pre-Islamic Arab women and its contextual connection to the development of Islamic family law.